The Curriculum Evaluation of Bachelor of Arts Degree in English (Revised 2016), the Faculty of Humanities, Mahamakut Buddhist University, Lanna Campus - แสนวังทอง, ธีรศักดิ์; ปภากโร, พระมหาสมชาย; เขมชีโว, พระมหาจุลชีพ; อธิปญโญ, พระมหาวีรเดช; คำมุงคุณ, ประดิษฐ์ (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
The purpose of this research article was to evaluate the curriculum of the Bachelor of Arts in English, Mahamakut Buddhist University:Lanna Campus. The samples were students, curriculum lecturers and instructors, using the purposive sampling. This evaluative research was based on the CIPP Model of Daniel L. Stufflebeam using both quantitative method and qualitative method. The tools used to collect the data were questionnaires and interview schedules. The research results were found that all 4 aspects were at the highest level. In each aspect, the product was in the highest level and the input was at the lowest level. The suggestions were as follow: each subject in the curriculum shouldn’t be the same content such as GE3004 English Translation and HU2005 English Translation, modern educational equipment and text book should be increased in order to be sufficient with the amount of the students, the Campus committee should set the program to train the instructors to use the study equipment and the technology used in teaching, supporting the curriculum advertisement, setting the activities to train the students The Journal of Humanities Vol.10 No.1 January – June 2018 125 to be the good people for all companies in order to encourage the students to have confidence in the program.